(untitled) (AYUSHDHARA, 2022)
The colorful surrounding can be perceived by individual with the help of Chakshurendriya i.e. eye. This sense organ acquires utmost importance as this is one of the vital sense perceptions for human beings. A 36 year old male patient was voluntarily selected for this study. He was diagnosed with Ashopha Akshipaka on the basis of symptoms wise burning sensation, sticky discharge, pricking sensation, heaviness, mild congestion, ocular pain and discomfort in both eyes. Viddha karma (bloodletting) is the only treatment modality selected for this study. Total 3 sittings of Viddhakarma (bloodletting) done consequentially for 3 days. Viddhakarma (bloodletting) done at the points described by Acharya Sushruta in Sushruta Nidana Sthana as Apang (Depression at lateral end of the eye brow), Lalate (on the forehead one and half finger above the eyebrow) and Upanasika (lateral aspect of alla). After first sitting Patient got relief, more than expected. Viddha karma (bloodletting) shows significant result in Ashopha Akshipaka and it helps in reducing the intensity of the symptoms in short period of time without any medicine.